Comparative Analysis of gO Isoforms Reveals that Strains of Human Cytomegalovirus Differ in the Ratio of gH/gL/gO and gH/gL/UL128-131 in the Virion Envelope - Zhou, Momei (American Society for Microbiology, 2013)
Herpesvirus glycoprotein complex gH/gL provides a core entry function through interactions with the fusion protein gB and can also influence tropism through receptor interactions. The Epstein-Barr virus gH/gL and gH/gL/gp42 serve both functions for entry into epithelial and B cells, respectively. Human cytomegalovirus (HCMV) gH/gL can be bound by the UL128-131 proteins or gO. The phenotypes of gO and UL128-131 mutants suggest that gO-gH/gL interactions are necessary for the core entry function on all cell types, whereas the binding of UL128-131 to gH/gL likely relates to a distinct receptor-binding function for entry into some specific cell types (e.g., epithelial) but not others (e.g., fibroblasts and neurons). There are at least eight isoforms of gO that differ by 10 to 30% of amino acids, and previous analysis of two HCMV strains suggested that some isoforms of gO function like chaperones, disassociating during assembly to leave unbound gH/gL in the virion envelope, while others remain bound to gH/gL. For the current report, we analyzed the gH/gL complexes present in the virion envelope of several HCMV strains, each of which encodes a distinct gO isoform. Results indicate that all strains of HCMV contain stable gH/gL/gO trimers and gH/gL/UL128-131 pentamers and little, if any, unbound gH/gL. TR, TB40/e, AD169, and PH virions contained vastly more gH/gL/gO than gH/gL/UL128-131, whereas Merlin virions contained mostly gH/gL/UL128-131, despite abundant unbound gO remaining in the infected cells. Suppression of UL128-131 expression during Merlin replication dramatically shifted the ratio toward gH/gL/gO. These data suggest that Merlin gO is less efficient than other gO isoforms at competing with UL128-131 for binding to gH/gL. Thus, gO diversity may influence the pathogenesis of HCMV through effects on the assembly of the core versus tropism gH/gL complexes.